Classification of Translation Transformations and their Practical Application in “To Have and Have Not” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores J. C. Catford’s theory of translation transformations and its practical application. Ernest Hemingway’s To Have and Have Not and its Uzbek translation have been chosen as the object of study. A comparative analysis of the source text and the target text is carried out to identify the lexical and grammatical transformations employed, which are examined in the light of J. C. Catford’s classification of translation shifts. Furthermore, the article discusses issues of preserving the author’s style, the degree of semantic equivalence, and the reconstruction of linguistic features in the process of translation. The findings highlight the significance of transformation theory in translation studies and demonstrate effective ways of applying transformations in the translation of literary works.